When home and work are not enough. The challenge of international migrants’ agency in the Italian Alps - Andrea Membretti; Fabio Lucchini; Monica Gilli; Mia Scotti (European Journal of Spatial Development)
Even when they have access to housing and employment, international migrants struggle to develop their own agency, i.e. the capacity to act in their own life contexts, exercising citizenship rights within substantive inclusion processes in the wider communities. The territorial context in fact, especially in rural and mountainous areas such as the Alpine ones analysed here, seems in many ways to represent a limit to the development of capacities and exercise of rights. Difficulties in accessing public space and public sphere, scarce social recognition, low status, housing isolation (as is the case of those who live in small mountain villages), professional ghettoisation: these are factors that, even in presence of an acceptable working and housing inclusion, make it difficult for international migrants to exercise their rights, to have their skills recognised, and, ultimately, to develop an agency genuinely linked to their capabilities.